AGRICULTURA FAMILIAR E PROGRAMA DE AQUISIÇÃO DE ALIMENTOS: UMA ANÁLISE DE SUA IMPLANTAÇÃO NO MUNICÍPIO DE PONTA GROSSA - Santos, Adriana Timoteo dos (2010)
The work has for purpose to analyze the process of implantation of the Program of Acquisition of Foods of Familiar Agriculture – PAA, in the modality Direct Purchase, the city of Ponta Grossa - PR, being emphasized the paper and the perceptions of the local social actors. The present program is one of the actions developed for the federal government through the Program Hunger Zero – PHZ, which objective to stimulate and to fortify familiar agriculture through the purchase of the production of the familiar and seated agriculturists of the agrarian reform, to assist the local development and to supply the food demand offered for social institutions and programs. It was used methodology of qualitative exploratory research, beyond bibliographical survey and research of field. The central hypothesis of that the PAA can become the more dynamic local territory for activating the economy, diversifying the production and to brighten up the situation of alimentary unreliability. From the conceptualization of territory and the quarrel of the public politics directed to the territorial development and the improvement of familiar agriculture, one searched to value the production and the endogenous development. It was evidenced genese of the PHZ and its functioning in the spheres federal, state and municipal, together with the origin and evolution of the concept of alimentary security related the support of the agricultural productive system. It is finished concluding that even so the process of implantation of the program in the studied city if has shown disarticulated and contradictory, observed that it fortifies familiar agriculture opening new line of commercialization, diversifying the production, increasing the income of the participant families and promoting the improvement of the alimentary and nutricional security of the people in situation of social risk. It is standed out that in function of the small number of involved agriculturists in Ponta Grossa, the territorial impact is relatively restricted.